Domestication and gonad maturation technique of Thynnicthys thynnoides Blkr obtained from the Kampar River, Riau - Sukendi '; Ridwan Manda Putra; Yurisman ' (Universitas Riau, 2009)
A study aims to find out the domestication and triggering gonadal maturation techniques of Thynnicthys thynnoides obtained from Kampar River, Riau has beenconducted from June to August 2009. Fish samples were kept in 1 x 1 x 1 m cages,30 fishes/ cage. Fishes were fed on three types of food namely dried Tubifex, shrimppellet (without vitamin E addition) and shrimp pellet that is enriched with vitamin E(100 gram/ kg ). The food provided was 5% of total fish body weight/ day.Result shown that fish domestication can be conducted by keeping them in the cagesthat are placed in the area where the fish are captured. During the first week, fisheswere not fed and in the following weeks they were provided with the treated fed. Thebest result obtained in the fishes that are feed with shrimp pellet that is enrichedwith vitamin E. During the research period (8 weeks), 12 fishes were sampled and 5of them were in the 4th gonadal maturity level, their maturity indices was 15.603%,fecundity 19,516 eggs, egg diameter 1.07 mm and semen volume produced 0.945 ml.Key words : domestication, maturity indeces, fecundity egg diameter